Resistome and microbial profiling of pediatric patient's gut infected with multidrug-resistant diarrhoeagenic Enterobacteriaceae using next-generation sequencing; the first study from Pakistan. Issue 1 (1st January 2021) - Afridi, Ome Kalsoom; Ali, Johar; Chang, Jeong Ho
ABSTRACT: A high prevalence of multidrug-resistant (MDR) pathogens has been reported in adult and pediatric populations of Pakistan. However, data describing the effect of MDR microbes on the gut microbiota is scarce. We designed a cross-sectional pediatric study to investigate the effect of MDR microbes' infection on the gut microbiome and its resistome of children using high-throughput next-generation sequencing (NGS). A cross-sectional study was conducted at a tertiary health care hospital in Peshawar Pakistan, between 5 September 2019 to 15 February 2020. Pediatric patients with acute gastroenteritis (n = 200) were enrolled. All the enrolled pediatric patients underwent initial antimicrobial resistance (AMR) screening using the disk diffusion method. Children with MDR infections were identified and selected for gut microbiome and its resistome profiling using NGS. Out of 200 enrolled pediatric patients, 80 (40%) were found infected with MDR diarrheagenic Enterobacteriaceae consisting of 50 (62.5%) infections caused by extended-spectrum beta-lactamase (ESBL) producing E. coli while 30 (37.5%) by MDR Enterobacter specie. A total of 63 and 17 antibiotic-resistant genes (ARGs) conferring resistance to 7 and 5 classes of antibiotics were identified in the resistomes of MDR diarrheagenic Enterobacteriaceae infected and healthy children, respectively. NGS-based gut microbial profiling of MDR Enterobacter spp ., ESBL producing E. coli infected pediatric patients and healthy controls revealed the predominance of Proteobacteria and Actinobacteria, respectively. An increased abundance of several pathogenic gram-negative bacteria namely E. coli, Enterobacter cloacae, and Salmonella enterica was observed in the gut microbiota of children infected with MDR bacterial infections than that of the healthy controls. This work indicates that children with MDR infections have reduced microbial diversity and enriched ARGs than healthy controls. The emergence of MDR bacterial strains and their association with gut dysbiosis needs immediate attention to regulate antibiotics usage in Pakistani children.